Television in Turkey’sRestructringProcess: Control andDissemination of TelevisionBroadcasting in thePeriodafterMarch 12, 1971 - İlaslan, Süleyman (Karadeniz Teknik Üniversitesi, 2014)
In 1970’s many developments took place in Turkey, which may be named as the basis for various substantial developments to take place in the future. At those times the television had developed rapidly both in the industrial and broadcasting senses, and it became accessible almost all over Turkey. As a result of the concern caused by the power of it, the television had become the subject of dense political interventions and struggles for control; and it took its place in the core of the negotiations on broadcasting. With this study, we are asserting that the first years of the 1970’s, especially the period between 1971 and 1973, have a critical importance in the sense of determining the limits of broadcasting in Turkey, and television’s becoming widespread of the as an industrial meta. The basic criteria and reference we used to identify the limits of our study are the initiation of a restructuring period for the capital after March 12th, 1971; and the indicators showing that 1973 is the beginning of a new era for Turkey.

Türkiye’de 1970’ler birçok gelişmeyi beraberinde getirmiş ve ilerleyen yıllarda yaşanacak köklü dönüşümlerin izlerini taşımıştır. Televizyonun gerek endüstriyel gerekse yayıncılık anlamında hızlı bir gelişim göstermesi ve neredeyse tüm Türkiye’den erişilebilir bir hale gelmesi de bu döneme denk gelmiştir. Televizyon, gücünden duyulan endişeyle daha yoğun kontrol mücadelelerinin ve politik müdahalelerin konusu haline gelmiş ve yayıncılık tartışmalarının merkezine yerleşmiştir. Bu çalışmada 1970’lerin ilk yıllarının Türkiye’de televizyon yayıncılığının sınırlarının belirlenmesi ve televizyonun endüstriyel bir meta olarak yaygınlaşması açısından kritik önemde olduğu ileri sürülmekte ve bu kapsamda 1971-1973 yılları inceleme kapsamına alınmaktadır. 12 Mart 1971’in sermaye açısından bir yeniden yapılanma döneminin başlangıcı olması ve 1973 yılının Türkiye açısından yeni bir döneme geçileceğinin sinyallerini vermesi çalışmamızın sınırlarını belirlemek açısından kıstas alınan temel noktalar olmuştur.
TÜRKİYE’NİN YENİDEN YAPILANMA SÜRECİNDE TELEVİZYON: 12 MART 1971 SONRASI DÖNEMDE TELEVİZYON YAYINCILIĞININ KONTROLÜ VE YAYGINLAŞTIRILMASI
Keywords: Communication and Media Studies; İletişim ve Medya Çalışmaları